Diversity and abundance of lignicolous marine fungi from the east and west coasts of Peninsular Malaysia and Sabah (Borneo Island) - Pang, Ka-Lai; Sharuddin, S.S.; Alias, S.A.; Nor, N.A.M.; Awaluddin, H.H. (Walter De Gruyter & Co, 2010)
We documented the diversity of marine fungi in various mangroves from the east and west coasts of Malaysia in the period May 2008-June 2009; we sampled at Cape Rachado, Morib, Redang Island, Bachok and Cape Layak-Layak. A total of 438 samples were examined. These comprised prop roots, pneumatophores, subterranean roots, rhizomes, overhanging branches and twigs of mangrove trees and driftwood. Seventy-seven higher marine fungal taxa were recorded, comprising 58 ascomycetes, two basidiomycetes and 17 anamorphic fungi. Among these, 38 were only partially identified/unidentified, indicating these might be new species. The most common species (> 10% occurrence) were Aigialus grandis, A. parvus, Dactylospora haliotrepha, Kallichroma tethys, Halocyphina villosa, Verruculina enalia and Ascocratera manglicola. Species diversity and richness were highest in Bachok, while Cape Layak-Layak had the highest species evenness. Sorenson's similarity indices between sites were low, implicating low similarity between fungal communities among the study sites.